The Effect of Ladder Drill Side Right in Training on Increasing the Agility of the Futsal Team of SMKN 1 Kandangan - Aryadi Rachman; Hafidz Mukti Ramadhan; Lutfi Yannor (Journal Coaching Education Sports, 2024)
This study aims to determine the effect of ladder drill side right in training on improving agility in the futsal team of SMK Negeri 1 Kandangan. Pre-experimental was used as the research method and Pretest and Posttest in One Group as the research design. All 16 members of the SMK Negeri 1 Kandangan futsal team were the population of this study. Illinois Agility Run Test is an instrument used to measure agility. The results of the t-test analysis showed that after receiving ladder drill side right in training, the player's agility increased significantly, with the value of tcount = 15.96 which is greater than ttable = 2.13. In conclusion, the agility of the SMK Negeri 1 Kandangan futsal team increased due to ladder drill side right in training. Suggestions for coaches are to apply this form of training in a structured and disciplined manner.